IMPLIKASI PEMISAHAN KEKUASAAN TERHADAP STABILITAS PEMERINTAHAN - Thaher, Irmanjaya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Separation of powers is a fundamental principle of modern constitutional government, preventing the concentration of power and ensuring accountable, transparent, and democratic governance through the division of legislative, executive, and judicial functions that ensure mutual oversight. This study analyzes the implications of separation of powers on government stability through four dimensions: theoretical and philosophical foundations, the effectiveness of checks and balances mechanisms, the phenomenon of executive aggrandizement, and contextual factors in implementation from an international comparative perspective. The research methodology utilizes a systematic, structured, and comprehensive Systematic Literature Review (SLR) to identify, evaluate, and synthesize relevant scientific findings in a transparent and replicable manner. The research discussion demonstrates that separation of powers has a strong theoretical and philosophical foundation as an instrument of democratic stability, checks and balances mechanisms effectively prevent abuse of power, executive aggrandizement threatens constitutional balance, and the effectiveness of implementation is strongly influenced by historical, structural, and cultural factors in each country, requiring a contextual approach. The study concludes that separation of powers is fundamental to the stability of democratic governance through preventing the concentration of power and ensuring institutional accountability, with checks and balances as a preventive instrument for abuse of power, but the phenomenon of executive dominance requires firm constitutional reform, and effective implementation requires contextual strategies according to the specific conditions of each country.